STUDI EKSPERIMENTAL SIFAT MEKANIK BETON NORMAL DENGAN MENGGUNAKAN ABU DASAR LIMBAH HASIL PEMBAKARAN CAMPURAN CANGKANG DAN SERABUT KELAPA SAWIT SEBAGAI PENGGANTI AGREGAT HALUS - Fauzi Rahman; Dwika Bagus Setiyawan (Lambung Mangkurat University Press, 2020)
The purpose of this study was to obtain the optimum base ash content that can be used as a substitute for fine aggregate for concrete mixtures. In this study, mortar samples were made with variations of bottom ash as a substitute for fine aggregate ranging from 0%, 10%, 15%, 25%, 35%, and 50%. In addition, the compressive strength of mortar samples was tested at 3 days, 7 days, 14 days, 21 days, and 28 days. Furthermore, the concrete sample was also prepared with f’c set at 25 MPa. Concrete samples were tested at 3 days, 7 days, 14 days, 28 days and 56 days. From these results obtained the optimum compressive strength of mortar from a mixture with a base ash content of 10% at the age of 28 days which reached 9.57 MPa. However, this result is still below the normal mortar yield of 11.58 MPa. As for the concrete sample, the highest compressive strength was obtained at the age of 56 days, which was 29.06 MPa for concrete with a base ash content of 10%, while normal concrete was 35.01 MPa. The results of this study indicate that increasing the age of the concrete increases the compressive strength. The compressive strength of concrete with 10% bottom ash decreased before 28 days, but after 28 days the compressive strength was able to reach the targeted f’c of 25 MPa.